Introducing Systematic Patent Analysis as an Innovative Pedagogy Tool/Experiential Learning Project in HE Institutes and Universities to Boost Awareness of Patent-based IPR - Aithal P. S.; Shubhrajyotsna Aithal, (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: Research on Patent Analysis as an Innovative Pedagogy Tool/Experiential Learning Project in HE Institutes and Universities to Boost Awareness of Patent-based IPR" is being done to determine whether or not using patent analysis as a novel pedagogical strategy in higher education institutions is effective. Through hands-on interaction with actual patent data, this study seeks to determine how incorporating patent analysis into the academic curriculum can improve experiential learning and promote a deeper understanding of intellectual property rights (IPR). This study aims to contribute valuable insights that can guide educational practices, equip students with the necessary skills for the knowledge-based economy, and ultimately encourage innovation and entrepreneurship within the classroom by examining the effect of this novel pedagogy on students' awareness and comprehension of patent-related IPR. Method: An exploratory research method is used. The relevant information for exploring our idea of systematic patent analysis as an innovative pedagogy tool and experiential learning project in higher education institutions and universities are collected from scholarly articles using the Google search engine, Google Scholar search engine, and AI-based GPTs. Result and Discussion: The procedure for systematic patent analysis as an innovative pedagogy tool in the classroom and as a method of experiential learning for the students to create awareness, to convert their ideas into product or process-based patents during their studies in higher education institutions. The advantages, benefits, constraints, and disadvantages of adopting systematic patent analysis are analysed. The future implications and impact of systematic patent analysis as a pedagogical tool or experiential learning method are discussed. Originality/Value: Implementing a structured approach to patent analysis within higher education institutions facilitates the enhancement of meaningful contributions to the creation of innovative products or processes, thereby advancing the generation of new intellectual property rights (IPR) both for the institution and the nation. Type of the Research: Exploratory Research.